Incorporating patient‐reported outcomes in dose‐finding clinical trials. (3rd December 2019) - Lee, Shing M.; Lu, Xiaoqi; Cheng, Bin
Abstract : Oncology dose‐finding clinical trials determine the maximum tolerated dose (MTD) based on toxicity outcomes captured by clinicians. With the availability of more rigorous instruments for measuring toxicity directly from patients, there is a growing interest to incorporate patient‐reported outcomes (PRO) in clinical trials to inform patient tolerability. This is particularly important for dose‐finding trials to ensure the identification of a well‐tolerated dose. In this paper, we propose three extensions of the continual reassessment method (CRM), termed PRO‐CRMs, that incorporate both clinician and patient outcomes. The first method is a marginal modeling approach whereby clinician and patient toxicity outcomes are modeled separately. The other two methods impose a constraint using a joint outcome defined based on both clinician and patient toxicities and model them either jointly or marginally. Simulation studies show that while all three PRO‐CRMs select well‐tolerated doses based on clinician's and patient's perspectives, the methods using a joint outcome perform better and have similar performance. We also show that the proposed PRO‐CRMs are consistent under robust model assumptions.